GRAF DUAL ANTIPRISMA DAN DIMENSI METRIKNYA - FITRIANI, FENNY; CAHYANINGTIAS, SARI (E-Jurnal Matematika; Vol 10 No 1 (2021), 2021)
Dual graph is one form of graph that can only be formed from graphs whose edges do not intersect each other. One of the graphs that can be converted into dual graphs is the antiprism graph A m n   . Antiprism graph A m n    is a graph that is formed from the absorption of vertices in the prism graph P m n   . One of the operations performed on a graph is finding the metric dimension of the graph. These metric dimensions are looking to find a minimum cardinality value of the graph. This article discusses the metric dimensions of the dual antiprism graph  A' m,n . Dimanesion of dual antiprism graph A' m,n    is obtained in four conditions namely metric dimension when A' m,2 , metric dimension when  A' 3,n  with n  ?  3 , metric dimension at times  A'4 ,n  with n  ?  3  , and metric dimensions at times  A' m,n  with m  ?  5   and n  ?  3.